Eksperimen Pembelajaran Matematika Melalui Problem Solving Learning Dan Problem Posing Learning Ditinjau Dari Motivasi Siswa Terhadap Prestasi Belajar (Pada Siswa Kelas VII SMP Negeri 1 Colomadu Tahun Ajaran 2015/2016) - Prabawati, Nugraheni; , Dr. Sumardi, M.Si (2016)
This study aims to describe and analyze: (1) the effect of learning strategy of Problem Solving Learning (PSL) dan Problem Posing Learning (PPL) in mathematics achievement; (2) the effect of the motivation of students direct learning in mathematics achievement; (3) The interaction strategy of Problem Solving Learning (PSL) dan Problem Posing Learning (PPL) in termsof the motivation of students in mathematics achievement. The reseach was conducted students of VII Grade of SMPN 1Colomadu of even semester of Academic Year 2015/2016 with the population all students of VII a number of 267 students of class VII student. Type of the research is experiment with quasi experimental design. The class sample on reseach by using the strastified cluster random sampling. Methods of data collection use the test, questionnaire and documentation. Data analyzed using analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is effect strategy of Problem Solving Learning (PSL) dan Problem Posing Learning (PPL) in mathematics achievement with FA=8,6092(2) there is effectsof the motivation of students (high, medium, low) in mathematics achievement with FB =11,0805, (3) there is no interaction the learning strategy of Problem Solving Learning (PSL) dan Problem Posing Learning (PPL) in terms of the motivation of students in mathematics achievement with FAB=1,2547.